Sonneastro : Die Künstler aus Gugging. - Haus der Künstler, Maria Gugging (Wien : NÖ Landesmuseums, 1990)
Fischer, Johann ; Garber, Johann ; Hauser, Johann ; Kamlander, Franz ; Kernbeis, Franz ; Koller, Fritz ; Korec, Johann ; Reisenbauer, Heinrich ; Schmidt, Arnold ; etc.
Sonneastro : Die Künstler aus Gugging, Haus der Künstler, Gugging, 1990
boek